The Effect of the Digital Economy on Indecent Work in Indonesia 2019 - Yuniar Putri Awaliyah Risky; Nucke Widowati Kusumo Projo (Politeknik Statistika STIS, 2021)
The emergence of the digital economy is indicated to affect the employment sector. The job opportunities created by the digital economy provide an opportunity for workers to work in poor jobs, full of risks and indecent works. This study aims: first, to describe the economic digital and indecent work conditions in Indonesia. Second, to investigate the direct influence of infrastructure and digital media on the digital economy. Third, to examine the direct impact of the digital economy on indecent work. The data used is secondary data with observations from 34 provinces sourced from BPS and other ministries. Using the SEM-PLS analysis method, the results show that infrastructure and digital media positively impact the digital economy. Similarly, the digital economy, reflected by e-commerce sellers and buyers, has a positive and significant relationship to indecent work as reflected by Employment Excessive Working Time (EEWT), Precarious Employment Rate (PER), and non-union workers. It can be said that the increase in the digital economy influences the conditions of indecent work.